Ten‐year assessment of the 100 priority questions for global biodiversity conservation. Issue 6 (10th September 2018) - Jucker, Tommaso; Wintle, Bonnie; Shackelford, Gorm; Bocquillon, Pierre; Geffert, Jan Laurens; Kasoar, Tim; Kovacs, Eszter; Mumby, Hannah S.; Orland, Chloé; Schleicher, Judith; Tew, Eleanor R.; Zabala, Aiora; et al.
Abstract: In 2008, a group of conservation scientists compiled a list of 100 priority questions for the conservation of the world's biodiversity. However, now almost a decade later, no one has yet published a study gauging how much progress has been made in addressing these 100 high‐priority questions in the peer‐reviewed literature. We took a first step toward reexamining the 100 questions to identify key knowledge gaps that remain. Through a combination of a questionnaire and a literature review, we evaluated each question on the basis of 2 criteria: relevance and effort. We defined highly relevant questions as those that – if answered – would have the greatest impact on global biodiversity conservation and quantified effort based on the number of review publications addressing a particular question, which we used as a proxy for research effort. Using this approach, we identified a set of questions that, despite being perceived as highly relevant, have been the focus of relatively few review publications over the past 10 years. These questions covered a broad range of topics but predominantly tackled 3 major themes: conservation and management of freshwater ecosystems, role of societal structures in shaping interactions between people and the environment, and impacts of conservation interventions. We believe these questions represent important knowledge gaps that have received insufficient attention and may need to be prioritized in future research. Abstract : Article impact statement : Freshwater ecosystem conservation, role of social structures in human‐environment interactions, and impacts of conservation interventions remain important knowledge gaps in efforts to conserve global biodiversity.